Illness perceptions, depression and anxiety in informal carers of persons with depression: a cross-sectional survey. - Scerri, Josianne; Saliba, Therese; Saliba, George; Scerri, Christian A.; Camilleri, Liberato (Quality of Life Research, 2019)
Purpose: To examine the illness perceptions of informal carers of persons with depression, using the theoretical framework of Leventhal's Common-Sense Model (CSM) and to determine whether these illness perceptions are predictors of anxiety and depression, as measures of psychological well-being.Methods: A cross-sectional survey was conducted with 94 Maltese individuals caring for a person with depression within a community setting. The informal carers completed the modified Illness Perception Questionnaire (IPQS-Relatives version) and the Hospital Anxiety and Depression Scale (HADS). Data were analysed using descriptive statistics, Spearman's rank order correlations and ANCOVA regression models, to identify predictors of anxiety and depression respectively in the informal carers.Results: The informal carers perceived depression as a cyclical condition, having negative consequences on both the patient and on themselves. Participants perceived the causes of depression to be mainly psychosocial in nature and generally viewed the treatment as effective. Caring for a person with depression was perceived as having a considerable negative emotional impact on them. Years of caring was identified as a predictor of anxiety accounting for 20.4% of the variance, and timeline chronicity beliefs, consequences (relative) and illness coherence were identified as predictors of depression, accounting for 56.8% of the variance.Conclusion: Illness cognitions are significant predictors of depression, thereby suggesting that cognition-based interventions may be effective in targeting depression in these informal carers. Thus, health professionals should explore the carers' personal understanding of the disease, their timeline beliefs and the perceived consequences of providing care, as they relate to their psychological well-being.